Consumption of fruits and vegetables among older adults: findings from the ELSI‐Brazil study - Paula Bolbinski; Mary Anne Nascimento-Souza; Maria Fernanda Lima-Costa; Sérgio Viana Peixoto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract This study aimed to assess the prevalence of recommended consumption of fruits and vegetables and their associated factors in a national sample representative of the Brazilian population aged 60 or over. Baseline data from the Brazilian Longitudinal Study of Aging (ELSI-Brazil), conducted from 2015 to 2016, including 4,982 older individuals, were used. The recommended consumption of fruits and vegetables was assessed based on questions on the weekly and daily frequency of fruits, natural fruit juice, and vegetables. Intake of five or more servings of these foods on five or more days per week was considered as recommended consumption. Exploratory variables included socio-demographic characteristics, health behaviors, health conditions, and use of health services. Univariate and multiple logistic regression were used to examine the factors associated with the recommended consumption of fruits and vegetables. The prevalence of recommended consumption of fruits and vegetables was 12.9% (95%CI: 11.5-14.3). This consumption showed associations with gender (women - OR = 1.40; 95%CI: 1.08-1.82), age group (80 years or older - OR = 1.66; 95%CI: 1.16-2.37), education level (8 years or more - OR = 2.07; 95%CI: 1.51-2.86), smoking (former smokers - OR = 0.69; 95%CI: 0.55-0.85 and current smokers - OR = 0.50; 95%CI: 0.33-0.77) and medical appointments in the previous 12 months (OR = 1.88; 95%CI: 1.31-2.71). Our findings showed a low prevalence of the recommended consumption of fruits and vegetables among older Brazilian adults, drawing attention to the need for policies aimed at increasing this consumption in the studied population.